2006
DOI: 10.1021/cm061661j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural and Magnetic Characterization of Mixed Manganese−Copper n = 1 Ruddlesden−Popper Phases

Abstract: New n ) 1 Ruddlesden-Popper phases containing manganese and copper have been synthesized. Their structure has been investigated by X-ray and neutron powder diffraction and found to be tetragonal (I4/mmm) at temperatures down to 10 K. The series of materials La x Sr 2-x Mn 0.5 Cu 0.5 O 4 (x ) 0.75, 1, 1.25, 1.5) displays significant Jahn-Teller distortions of the B site cations, with the degree of distortion increasing with x. The materials LaSrMn 0.5 Cu 0.5 O 4 , PrSrMn 0.5 Cu 0.5 O 4 , and NdSrMn 0.5 Cu 0.5 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Manganese dioxides (MnO 2 ) are promising materials for many technological applications such as lithium batteries, oxidant agents, and catalysts. [1][2][3][4] Their high activities are ascribed to their tunnel and layered structures, which have edge-or corner-sharing [MnO 6 ] octahedra. Based on the law of varieties connectivity schemes, MnO 2 shows great structural exibility and appears in a number of crystallographic polymorphs such as a-, b-, and g-MnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Manganese dioxides (MnO 2 ) are promising materials for many technological applications such as lithium batteries, oxidant agents, and catalysts. [1][2][3][4] Their high activities are ascribed to their tunnel and layered structures, which have edge-or corner-sharing [MnO 6 ] octahedra. Based on the law of varieties connectivity schemes, MnO 2 shows great structural exibility and appears in a number of crystallographic polymorphs such as a-, b-, and g-MnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Rietveld refinement at 100 K using a model of I 4/ mmm symmetry gives unfeasibly large atomic displacement parameters (ADPs) for the equatorial anion site X 1 (and, to a lesser extent, the apical anion site X 2), (5.6(1) × 100 Å 2 and 3.7(1) × 100 Å 2 , respectively; see Supporting Information). Allowing these ADPs to refine anisotropically revealed significant displacements (either static or dynamic) of X 1 along [100] (consistent with rotation of Ti X 6 octahedra about [001]) and along [001] (consistent with rotation about an in-plane axis), similar to the displacive disorder observed in related systems. , Moving the equatorial and apical anions to lower symmetry sites ( X 1 from 4 c to 16 n and X 2 from 4 e to 16 m ) gave more reasonable ADPs (1.2(1) × 100 Å 2 and 0.82(9) × 100 Å 2 , respectively) and an improvement in fit [ R wp decreased from 6.95% (52 parameters) for the ordered model to 5.67% (55 parameters) for the displacive disordered model]. Refinement details and selected bond lengths are given in Table and refinement profiles in Figure , and the disordered structural model of I 4/ mmm symmetry is illustrated in Figure d.…”
Section: Resultsmentioning
confidence: 70%
“…Competitive ion-exchange reactions involving a mixed solution of CsCl and RbI showed that this site uniquely selects Cs + , with Rb + being exchanged onto a smaller site in the structure. All three sites are interconnected and the smallest site shows a good selectivity for NH 4 + which migrates through the larger sites in order to access this thermodynamically preferable position. This strong selectivity for caesium even in low concentrations compared to rubidium and ammonium suggests that this material may find applications in 137 71 Strontium cations in adjacent slabs are coordinated by either oxide or carbodiimide to form pillared structures.…”
Section: Halides Chalcogenides Nitridesmentioning
confidence: 99%
“…This distortion is propagated through the structure and results in a negative thermal expansion of 0.32% in the c parameter on cooling from room temperature to 3.5 K. Jahn-Teller distortions are also observed in the Ruddlesden-Popper phases La x Sr 2Àx Mn 1/2 Cu 1/2 O 4 (x = 0.75, 1, 1.25, 1.5). 4 These structures are conceptually related to perovskite and can be considered to contain sheets of Mn/CuO 6 perovskite separated by layers of rock salt to yield highly anisotropic electronic properties. All compounds showed chemical disorder of copper and manganese over a single crystallographic site.…”
Section: Oxidesmentioning
confidence: 99%